2019
DOI: 10.1038/s41416-019-0574-7
|View full text |Cite
|
Sign up to set email alerts
|

The lytic activity of VSV-GP treatment dominates the therapeutic effects in a syngeneic model of lung cancer

Abstract: BackgroundOncolytic virotherapy is thought to result in direct virus-induced lytic tumour killing and simultaneous activation of innate and tumour-specific adaptive immune responses. Using a chimeric vesicular stomatitis virus variant VSV-GP, we addressed the direct oncolytic effects and the role of anti-tumour immune induction in the syngeneic mouse lung cancer model LLC1.MethodsTo study a tumour system with limited antiviral effects, we generated interferon receptor-deficient cells (LLC1-IFNAR1−/−). Therapeu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…41 Hence, we used the B16 IFNAR -/- cells as it was shown that IFNAR deficiency prolongs virus replication. 22 Virus replication in the tumor was confirmed by in vivo bioluminescence imaging (BLI) using a VSV-GP variant expressing the firefly luciferase (VSV-GP-Luc). In comparison to the PBS treated group, i.t.…”
Section: Resultsmentioning
confidence: 99%
“…41 Hence, we used the B16 IFNAR -/- cells as it was shown that IFNAR deficiency prolongs virus replication. 22 Virus replication in the tumor was confirmed by in vivo bioluminescence imaging (BLI) using a VSV-GP variant expressing the firefly luciferase (VSV-GP-Luc). In comparison to the PBS treated group, i.t.…”
Section: Resultsmentioning
confidence: 99%
“…Variants of two of the viruses we used in the preceding experiments, VSV-GFP and Reovirus, are evaluated as potential virotherapy agents in a variety of solid tumors, including lung cancer (Schreiber et al, 2019 38 , Villalona-Calero et al, 2016 39 ). We therefore tested whether inhibition of the AKT/p-IWS1 axis enhances their cytolytic activity against tumor cells.…”
Section: Resultsmentioning
confidence: 99%
“…1, Fig. 2 ), which induces the alternative RNA splicing of U2AF2 (Laliotis et al, 2020 37 ). This shift in the alternative RNA splicing pattern controls the interaction of U2AF65 with yet another splicing factor, Prp19.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we focus on replication-competent Vesicular Stomatitis Virus (VSV) vectors, which have been shown to offer great promise as oncolytic agents mainly because (i) they are not pathogenic to humans and (ii) humans do not have pre-existing immunity against these viruses [26,3]. In regard to the interactions between these virus particles and the macrophages, various experimental studies have shown that immune protection against VSV infection is controlled by the induction of a type-I interferon response [53], and therefore, the M1 macrophages are likely to be involved in the elimination of VSV particles. Moreover, it is known that macrophages can be infected by the VSV [50,54].…”
Section: Introductionmentioning
confidence: 99%